The ethics of competition how a competitive society is good for all - Lütge, Christoph (Edward Elgar Publishing, 2019)
Contents: Introduction -- 1. Competition: terminology and concepts -- 2. The ethical role of competition -- 3. Is life a see-saw? Zero-sum thinking and moderation -- 4. Competition and ecology -- 5. Competition and education -- 6. Competition in health and nursing care -- 7. Competition, politics, and media -- 8. Competition in our daily lives -- 9. Conclusion -- Bibliography -- Index
Includes index
Includes bibliographical references
Keywords: Competition; Business ethics; Ethics; Gesellschaft; Wirtschaftsethik; Wettbewerb; Ethik; Electronic books